Effective alkaline metal-catalyzed oxidative delignification of hybrid poplar. Issue 1 (December 2016) - Bhalla, Aditya; Bansal, Namita; Stoklosa, Ryan; Fountain, Mackenzie; Ralph, John; Hodge, David; Hegg, Eric
Abstract Background Strategies to improve copper-catalyzed alkaline hydrogen peroxide (Cu-AHP) pretreatment of hybrid poplar were investigated. These improvements included a combination of increasing hydrolysis yields, while simultaneously decreasing process inputs through (i) more efficient utilization of H2 O2 and (ii) the addition of an alkaline extraction step prior to the metal-catalyzed AHP pretreatment. We hypothesized that utilizing this improved process could substantially lower the chemical inputs needed during pretreatment. Results Hybrid poplar was pretreated utilizing a modified process in which an alkaline extraction step was incorporated prior to the Cu-AHP treatment step and H2 O2 was added batch-wise over the course of 10 h. Our results revealed that the alkaline pre-extraction step improved both lignin and xylan solubilization, which ultimately led to improved glucose (86 %) and xylose (95 %) yields following enzymatic hydrolysis. An increase in the lignin solubilization was also observed with fed-batch H2 O2 addition relative to batch-only addition, which again resulted in increased glucose and xylose yields (77 and 93 % versus 63 and 74 %, respectively). Importantly, combining these strategies led to significantly improved sugar yields (96 % glucose and 94 % xylose) following enzymatic hydrolysis. In addition, we found that we could substantially lower the chemical inputs (enzyme, H2 O2, and catalyst), while still maintaining high product yields utilizing the improved Cu-AHP process. This pretreatment also provided a relatively pure lignin stream consisting of ≥90 % Klason lignin and only 3 % xylan and 2 % ash following precipitation. Two-dimensional heteronuclear single-quantum coherence (2D HSQC) NMR and size-exclusion chromatography demonstrated that the solubilized lignin was high molecular weight (Mw ≈ 22, 000 Da) and only slightly oxidized relative to lignin from untreated poplar. Conclusions This study demonstrated that the fed-batch, two-stage Cu-AHP pretreatment process was effective in pretreating hybrid poplar for its conversion into fermentable sugars. Results showed sugar yields near the theoretical maximum were achieved from enzymatically hydrolyzed hybrid poplar by incorporating an alkaline extraction step prior to pretreatment and by efficiently utilizing H2 O2 during the Cu-AHP process. Significantly, this study reports high sugar yields from woody biomass treated with an AHP pretreatment under mild reaction conditions.